Ta’lim Maharah al-Kalam ‘Ala Asas al-Tsaqafah bi Istikhdam Kitab al-‘Arabiyyah Bayna Yadayk fi Marhalah al-Mutawassithah - Ritonga, Apri Wardana; Wargadinata, Wildana; Ritonga, Mahyudin; Febriani, Suci Ramadhanti (Arabiyatuna: Jurnal Bahasa Arab, 2021)
This study encourages the disclosure of cultural values contained in the book al-‘Arabiyyah Baina Yadaik which is used in learning maharah kalam at the middle school level. Teaching cultural-based maharah kalam is important in learning Arabic. Cultural values contained in textbooks must be adapted to the way they are taught to students. This study used a qualitative approach with a case study method at Dar el-Iman Junior High School, Padang, Indonesia. Data collection was carried out using in-depth observations, interviews, and documentation. Meanwhile, the data analysis technique was based on Miles and Huberman's theory which encompassed data reduction, data display, and drawing conclusion. The data obtained were validated with data triangulation techniques and data sources. This study showed that the cultural values adopted from the book al-‘Arabiyyah Baina Yadaik in Junior High School of Dar el-Iman are associated with what students have done every day, such as saying greetings when they first meet, not shaking hands between men and women, getting used to good pronunciation of sentences, and etc. It is necessary to test the effectiveness of the use of al-‘Arabiyyah Baina Yadaik textbook in improving students' maharah kalam, to become a reference for teachers in choosing the right maharah kalam textbook.